2015
DOI: 10.1212/wnl.0000000000001557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of white matter lesions on manual dexterity in healthy middle-aged persons

Abstract: Objectives: We hypothesized that integrated motor-visual functions measured by manipulative manual dexterity are affected by white matter lesion (WML) burden as measured on cranial MRI across relevant brain regions in subjects at risk of preclinical occult vascular disease.Methods: A real-time cross-sectional study of healthy subjects aged 29 to 74 years with a family history of early-onset coronary artery disease (n 5 714; mean age, 51 6 11 years; mean education, 14 6 3 years; 42% male; 38% black) were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…A few previous studies have investigated the association of white matter structure and upper extremity functions. A population-based study 23 and a study conducted in families with a history of early-onset coronary artery disease 22 found greater WMH volume was associated with decreased manual dexterity (Grooved Pegboard Test). However, the two studies did not assess white matter microstructural integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few previous studies have investigated the association of white matter structure and upper extremity functions. A population-based study 23 and a study conducted in families with a history of early-onset coronary artery disease 22 found greater WMH volume was associated with decreased manual dexterity (Grooved Pegboard Test). However, the two studies did not assess white matter microstructural integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the lower extremity, manual dexterity was more important for fine motor skills in daily activities, such as feeding, dressing, and grooming, especially in the elderly 21 . Although sparse, exiting findings have also linked poor manual dexterity and worse finger task performance to greater white matter hyperintensities (WMH) 22 , 23 volume and disrupted white matter tract integrity 24 , 25 . Few studies have investigated how upper extremity and lower extremity functions relate to brain structural lesions in the same sample 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Their shapes are deformable, their location and area across patients may differ significantly [25]. There are many automatic and semiautomatic approaches for brain segmentation [6, 7], Similar to those methods, the MS lesions segmentation approaches include a variety of methods such as region partitioning, markov random field model, adaptive outlier detection and feature extraction [8–11].…”
Section: Introductionmentioning
confidence: 99%
“…In a prior cross-sectional study of 563 cognitively normal middle-aged relatives, we found a high prevalence of early white matter hyperintensity lesions (WMHL) [13], and further, observed lower cognitive function scores among those with higher WMHL volumes [4]. Most prior WMHL studies have occurred in the elderly or in populations with dementia [5].…”
mentioning
confidence: 99%
“…All volumes were measured with an automated standard pipeline as described previously [3]. Cognitive function was measured using standard tests, [4] and traditional vascular risk factors were assessed. Changes over 5 years are presented on the Table.…”
mentioning
confidence: 99%